2012
DOI: 10.2174/1381612811209023007
|View full text |Cite
|
Sign up to set email alerts
|

Ibubrofen in the Treatment of Patent Ductus Arteriosus in Preterm Infants: What We Know, What We Still Do Not Know

Abstract: The patency of the ductus arteriosus has ever been considered as a pathological situation in preterm infants and one likely cause of mortality and morbidity, including broncho-pulmonary dysplasia, necrotizing enterocolitis, intraventricular haemorrhage, retinopathy of prematurity. The incidence of patent ductus arteriosus is inversely proportional to gestational age and infants with the lowest gestational ages are the most exposed to the complications of prematurity. So, associations between patent ductus arte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…The patency of the ductus arteriosus has ever been considered as a pathological situation in preterm infants and one likely cause of mortality and morbidity, including bronchopulmonary dysplasia, necrotizing enterocolitis, intraventricular hemorrhage, and ROP. 6 Prostaglandin E2 has the opposite effect to that of oxygen; it relaxes smooth muscle and tends to inhibit the closure of the ductus arteriosus. Non-steroidal anti-inflammatory agents, such as indomethacin or ibuprofen, have been shown to be effective in closing or preventing PDA, with differences in side effects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The patency of the ductus arteriosus has ever been considered as a pathological situation in preterm infants and one likely cause of mortality and morbidity, including bronchopulmonary dysplasia, necrotizing enterocolitis, intraventricular hemorrhage, and ROP. 6 Prostaglandin E2 has the opposite effect to that of oxygen; it relaxes smooth muscle and tends to inhibit the closure of the ductus arteriosus. Non-steroidal anti-inflammatory agents, such as indomethacin or ibuprofen, have been shown to be effective in closing or preventing PDA, with differences in side effects.…”
Section: Discussionmentioning
confidence: 99%
“…The major factor closing the ductus arteriosus is the tension of oxygen, which increases significantly after birth. The patency of the ductus arteriosus has ever been considered as a pathological situation in preterm infants and one likely cause of mortality and morbidity, including broncho-pulmonary dysplasia, necrotizing enterocolitis, intraventricular hemorrhage, and ROP 6…”
Section: Discussionmentioning
confidence: 99%
“…As a result, emphasis has been placed on targeted pharmacotherapeutic treatment of PDAs when deemed hemodynamically significant by the clinician based on clinical and echocardiographic parameters . However, lack of pharmacokinetic and pharmacodynamic data on nonsteroidal anti-inflammatory drug use in preterm infants has led to the use of different drugs in varying doses and routes of administration . The 2 most commonly used treatment options are standard doses of intravenous ibuprofen and intravenous indomethacin …”
Section: Introductionmentioning
confidence: 99%
“…However, lack of pharmacokinetic and pharmacodynamic data on nonsteroidal anti-inflammatory drug use in preterm infants has led to the use of different drugs in varying doses and routes of administration . The 2 most commonly used treatment options are standard doses of intravenous ibuprofen and intravenous indomethacin …”
Section: Introductionmentioning
confidence: 99%
“…Pharmacological treatment consists of using non-steroidal anti-inflammatory drugs (NSAIDS), typically Indomethacin or Ibuprofen. There is an ongoing debate about which of the two NSAIDS is best suited for this intervention [ 2 ]. A Cochrane review published in 2015 suggested Ibuprofen to be as effective as indomethacin in closure efficacy but with reduced renal and gastric complications, thereby making it an agent of choice in many neonatal units [ 3 ].…”
Section: Introductionmentioning
confidence: 99%